Efficient Secretion and Recombinant Production of a Lactobacillal α-amylase in Lactiplantibacillus plantarum WCFS1: Analysis and Comparison of the Secretion Using Different Signal Peptides - Tran, Anh-Minh; Unban, Kridsada; Kanpiengjai, Apinun; Khanongnuch, Chartchai; Mathiesen, Geir; Haltrich, Dietmar; Nguyen, Thu-Ha (Frontiers in Microbiology, 2021)
Lactic acid bacteria (LAB) have been used as starter cultures and producers of enzymes, antimicrobial peptides or metabolites that contribute to the flavor, texture and safety of food products. Lactiplantibacillus plantarum, one of the best-studied LAB, is considered as safe and effective cell factory for food applications. In this study, our aim was to use L. plantarum as the producer for high levels of a food-grade lactobacillal α-amylase, which has potential applications in food, fermentation and feed industries. The native form of an α-amylase (AmyL) from L. plantarum S21, an amylolytic LAB isolated from Thai fermented rice noodles, was expressed in L. plantarum WCFS1 using the pSIP expression system. The secretion of the α-amylase was driven by the native signal peptides of the α-amylases from L. plantarum S21 (SP_AmyL) and Lactobacillus amylovorus NRRL B-4549 (SP_AmyA), as well as by three Sec-type signal peptides derived from L. plantarum WCFS1; Lp_2145, Lp_3050, and Lp_0373. Among the tested signal peptides, Lp_2145 appears to be the best signal peptide giving the highest total and extracellular enzymatic activities of α-amylase AmyL from L. plantarum S21, which were 13.1 and 8.1 kU/L of fermentation, respectively. These yields were significantly higher than the expression and secretion in L. plantarum WCFS1 using the native signal peptide SP_AmyL, resulting in 6.2- and 5.4-fold increase in total and extracellular activities of AmyL, respectively. In terms of secretion efficiency, Lp_0373 was observed as the most efficient signal peptide among non-cognate signal peptides for the secretion of AmyL. Real-time reverse-transcriptase quantitative PCR (RT-qPCR) was used to estimate the mRNA levels of α-amylase transcript in each recombinant strain. Relative quantification by RT-qPCR indicated that the strain with the Lp_2145 signal peptide-containing construct had the highest mRNA levels and that the exchange of the signal peptide led to a change in the transcript level of the target gene.